(untitled) (ARTEKS : Jurnal Teknik Arsitektur, 2026)
This study examines the empowerment of older adults within urban public spaces as a strategic initiative to enhance social resilience. Despite the presence of comprehensive national and regional policy frameworks, a substantial gap is evident between policy formulation and its practical implementation on the ground. Adopting a descriptive qualitative approach and case studies in Malang City, data were collected through in-depth interviews, direct field observations, and systematic reviews of policy documents. The findings reveal that city parks have not yet functioned as inclusive and empowering environments for elderly users. The inability to meet accessibility standards, including safe pedestrian pathways, adequate handrails, and comfortable seating facilities, reflects the weak execution of existing policies. Furthermore, the limited availability of park-based social activities highlights a lack of integration between policy frameworks and empowerment programs. This study concludes that the physical revitalization of city parks must be integrated with sustainable social programs to realize inclusive social resilience. The research recommendations emphasize the importance of cross-sector coordination, dedicated budgeting, and participatory programs as key measures to bridge the gap between policy intentions and the implementation of senior-friendly parks.